HUBUNGAN KEPERCAYAAN DIRI DENGAN KOMUNIKASI INTERPERSONAL PADA MAHASISWA ANGKATAN 2013 PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS SAM RATULAGI MANADO - Rewah, Kristi A.; Palandeng, Henry; Bawotong, Jeavery (JURNAL KEPERAWATAN, 2014)
Abstract: Background In the interpersonal communication, confidence is needed because the recognition and appreciation of communication we will have if we have the confidence..Purpose to know The Relationship Between Interpersonal Communication with Confidence for Student class 2013 at Nursing Department, Sam Ratulangi University Manado. Design is observational analytic with approach cross sectional. Population entire student class of 2013 at Nursing Department, Sam Ratulangi University, with number 109 students and Sample use purposive sampling, with number 57 students. The data collected were processed using SPSS computer assistance (Statistical Programme For Social Science) version 20 using the chi-square test at 95% significance level (á 0.05).Result obtained value of P =0,152 more than á = 0,05 (p 0,05).Conclusion there is not relationship between interpersonal communication with confidence for student class 2013 at Nursing Department, Sam Ratulangi University Manado. Suggestion consideration for the department as teaching materials for courses Psychiatric Nursing, and the student is expected to improve the knowledge about confidence and interpersonal communication, Keywords: Confidence, Interpersonal Communication Abstrak: LatarBelakang Dalam berkomunikasi antar pribadi kepercayaan diri sangat dibutuhkan, karena pengakuan dan penghargaan dalam berkomunikasi akan kita miliki, jika kita memiliki kepercayaan diri. Tujuan Penelitian ini untuk mengetahui hubungan antara kepercayaan diri dengan komunikasi interpersonal pada mahasiswa angkatan 2013 di Program Studi Ilmu Keperawatan Universitas Sam Ratulangi Manado. Desain penelitian adalah observasional analitik dengan pendekatan cross sectional. Populasi seluruh Mahasiswa angkatan 2013 Program Studi Ilmu Keperawatan Universitas Sam Ratulangi, dengan jumlah 109 mahasiswa dan sampel penelitian menggunakan purposive sampling, dengan jumlah 57 mahasiswa. Data yang dikumpulkan, diolah dengan menggunakan program SPSS (Statistical Program For Social Science) versi 20 menggunakan uji chi-square pada tingkat kemaknaan 95% (á 0,05). Hasil penelitian ini didapat nilaiP = 0,152 lebih besar dari nilai á = 0,05 (p 0,05).Kesimpulantidak ada hubungan antara kepercayaan diri dengan komunikasi interpersonal Mahasiswa angkatan 2013 Program Studi Ilmu Keperawatan Universitas Sam Ratulangi Manado. Saranbagi Program Studi sebagai pertimbangan bahan ajar untuk mata kuliah Keperawatan Jiwa, dan bagi mahasiswa diharapkan dapat meningkatkan pengetahuan mengenai kepercayaan diri dan komunikasi interpersonal. Kata kunci: kepercayaan diri, komunikasi interpersonal